The social benefits of initial vocational education and training for individuals in Europe - Sabates, Ricardo [Verfasser]; Salter, Emma [Verfasser]; Obolenskaya, Polina [Verfasser] (My University, 2012)
"This article investigates the social benefits of initial vocational education and training (VET) for individuals in different European contexts. Drawing on data from the European Community Household Panel, results show that initial VET is associated with positive changes in social outcomes for individuals across Europe. Health benefits were mainly found in egalitarian contexts such as Sweden whereas benefits in terms of civic participation were mainly found in countries that reward participation in civil society such as Sweden and Austria or where participation in voluntary activities may be seen as an insurance to avoid falling into unemployment, for instance in Italy, Greece, and Spain. Overall, the benefits of initial VET for individuals are possibly where there are institutional factors that support the formation of these benefits." (Autorenreferat, BIBB-Doku)
Keywords: S 4.3.6 Human Capital; T 4.5 Soziologie; I 2.2 Europa; Berufsausbildung; Bildungsertrag; Sozialkapital; Individuum; Indikatoren; Gesundheit; Ehrenamt; Ehrenamtliche Tätigkeit; Quantitative Angaben; Internationaler Vergleich; Europa; 1994-2001